Hard X‐ray self‐seeding commissioning at PAL‐XFEL. (18th June 2019) - Min, Chang-Ki; Nam, Inhyuk; Yang, Haeryong; Kim, Gyujin; Shim, Chi Hyun; Ko, Jun Ho; Cho, Myung-Hoon; Heo, Hoon; Oh, Bonggi; Suh, Young Jin; Kim, Min Jae; Na, Donghyun; et al.
Abstract : Hard X‐ray self‐seeding based on a diamond wake monochromator has been commissioned at PAL‐XFEL using various bunch charges and crystals. The performances of self‐seeding and low electron‐energy jitter (∼10 −4 ) are discussed. Abstract : A wake monochromator based on a large‐area diamond single crystal for hard X‐ray self‐seeding has been successfully installed and commissioned in the hard X‐ray free‐electron laser (FEL) at the Pohang Accelerator Laboratory with international collaboration. For this commissioning, the self‐seeding was demonstrated with a low bunch charge (40 pC) and the nominal bunch charge (180 pC) of self‐amplified spontaneous emission (SASE) operation. The FEL pulse lengths were estimated as 7 fs and 29.5 fs, respectively. In both cases, the average spectral brightness increased by more than three times compared with the SASE mode. The self‐seeding experiment was demonstrated for the first time using a crystal with a thickness of 30 µm, and a narrow bandwidth of 0.22 eV (full width at half‐maximum) was obtained at 8.3 keV, which confirmed the functionality of a crystal with such a small thickness. In the nominal bunch‐charge self‐seeding experiment, the histogram of the intensity integrated over a 1 eV bandwidth showed a well defined Gaussian profile, which is evidence of the saturated FEL and a minimal electron‐energy jitter (∼1.2 × 10 −4 ) effect. The corresponding low photon‐energy jitter (∼2.4 × 10 −4 ) of the SASE FEL pulse, which is two times lower than the Pierce parameter, enabled the seeding power to be maximized by maintaining the spectral overlap between SASE FEL gain and the monochromator.